A Review of Deontic Modality in Indonesian Language Based on the theory of Japanese Modality - Tatang Hariri (Humaniora, 2011)
According to Hasan Alwi (1992) the scopes of deontic modality in Indonesian are permission and command with its modals such as .boleh, bisa, dapat., and other modality verbs. These two meanings, permission and command, are investigated from the point of view predication and deictivity. In this study deontic modality in Indonesian will be reviewed on the basis of the theory of Japanese modality.